Simultaneous PET/MRI: Impact on cancer management-A comprehensive review of cases - Amarnath Jena (Indian Journal of Radiology and Imaging, 2014)
The metabolic mapping of malignancy in whole body in a single examination by PET/CT has gained widespread acceptance where the CT provides an anatomical correlate for the PET. MRI offers advantage over CT in providing better anatomical information owing to its high soft tissue resolution especially in brain, liver, neck, pelvis and bone marrow. Simultaneous PET/MRI is a new multimodal imaging modality that is expected to improve the diagnostic performance of imaging wherein better anatomical and metabolic information can be acquired at the same time and space during a single examination time. Also, MR attributes like diffusion, perfusion and spectroscopy may further add to its diagnostic potential. In this article, we present our initial experience in illustrated cases done with simultaneous PET/MRI and outline its potential for several clinical applications in oncology.